A diversidade de insetos madícolos em montanhas de mata atlântica : uma abordagem ecológica e taxonômica - Shimabukuro, Erika Mayumi (Universidade Federal de São Carlos, 2017)
Ecologists all over the world have long been interested in studying mountains. Many factors explain the importance of mountain ecosystems as models to test patterns of spatial variation of biological communities: 1. Along altitudinal gradients significant climate changes can be observed in a relatively short spatial scale; 2. Comparing to oher spatial gradients, e.g. latitude, experiments developed in mountains are easily replicable; 3. The isolation and proximity from other mountains, as well as the noticeable climatic and geologic events that they experience, ensure the high biogeographical value of mountains; 4. Mountains guarantee ideal conditions for the establishment of a remarkable biodiversity, facilitating speciation process and the survivor of rare and endemic species. Regarding these factors, the main objective of this study was to assess patterns of richness and dissimilarity variations along altitudinal gradients at Atlantic Forest from Southeast Brazil. The madicolous (hygropetric) insect community and three mountains located at Serra do Mar and Serra da Mantiqueira – compounding a gradient from 0 m to 2700 m a.s.l. 0 were the study object of this work. At the first part of the thesis (ecologic approach), important hypotheses of richness and dissimilarity’ variations along altitudinal gradients have been tested: 1 Rapoport’s effect; 2. Spatial effect; 3. Environmental control; 4. “Mountain Passes are Higher in the Tropics”; 5. Source-sink dynamics. As madicolous habitats shelter a peculiar fauna of insects, and poorly addressed in literature, in the second part of the thesis (taxonomic approach), a checklist of all madicolous Chironomidae recorded here is presented. In addition, new species belonging to three Chironomidae genera are described and new records were evidenced. Madicolous insects are extremely diverse, and most of the taxa that compound it are the same found in insect community from streams. A significant variation of richness and dissimilarity have been observed along the gradients analyzed, and further, this variables showed deeply related to the gradients’ altitude. Regarding the madicolous Chironomidae community, many species unknown to science have been verified, many of them with restricted altitudinal distribution. In addition, many known species have been recorded for the first time in this peculiar habitat. These results confirm the importance and the need of conservation and monitoring of mountain ecosystems, especially at tropical region, where climatic impacts and anthropic pressure tend to be harsher.
Keywords: Insetos; Ecologia das montanhas; Ecossistemas; Insects; Mountain ecology; Biotic communities; CIENCIAS BIOLOGICAS::ECOLOGIA